On some argumentative modifications in logic (Actual Problems of Mind, 2022)
Abstract. The reorientation of logical research from the analysis of individual sentences to the analysis of argument systems leads to some changes in logic itself. Such a reorientation is due to the features of plausible arguments put forward to support decision-making. One such feature is that applying the rules of inference does not guarantee that the conclusion of a plausible argument is justified. It is necessary to explain how exactly the transition from the premises to the conclusion of such an argument takes place. It must be established that the transmission of the justification from the premises to the conclusion with the help of the rules of inference really took place. It depends on this whether the individual is committed to accepting the conclusion and applying it in his further reasoning.The basis for accepting the conclusion of a plausible argument as justified is a successful defense against counterargument attacks. The introduction of the means of presentation of the competition of arguments into the logic is one of the features of its communicative transformation.The conclusions of plausible arguments are justified only to a certain extent. It is recommended not to strive for full justification of conclusions, but to establish only the degree of their justification, precisely because of the incompleteness of information, presented in the premises of such arguments.In the semantics used to justify the conclusions of plausible arguments, the premises and rules of inference are assigned degrees of conviction. They reflect the strength of these structural components of arguments. And the justification of the conclusion of the argument is calculated on the basis of assigning degrees of conviction to its components and components of its counterarguments.Argumentation depends on values, so the database used to build arguments must also contain information about them. Just like beliefs, values ​​can also have degrees. Semantic rules for calculating the degree of justification of conclusions should take these degrees into account. Logical semantics, modified in this way, appears to be the most suitable tool for evaluating practical plausible arguments, and in particular for answering critical questions raised about such arguments.
Keywords: argumentation schemes; evaluations; degrees of conviction; the transmission of justification; plausible arguments; degrees of values